The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1116/1.569107
|View full text |Cite
|
Sign up to set email alerts
|

Self-sputtering phenomena in high-rate coaxial cylindrical magnetron sputtering

Abstract: In order to increase the deposition rate in magnetron sputtering, end plates were attached to both ends of cylindrical target. A current density of 0.1 A/cm2 was obtained with relatively low target voltage from 300 to 800 V. Deposition rates of Al and Cu were measured as functions of target voltage and current. From a discrepancy between measured and calculated values based on sputtering yield data, it is considered that sputtered Al atoms were ionized in a high density argon plasma and that the target was bom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…For selected target materials with very high sputtering yield and/or vapor pressure (like Cu, Ag, Bi, Zn), high power operation of a magnetron can readily lead to ionization of the sputtered atoms, and the newly formed metal ions can at least in part take over the function of the sputtering gas (often argon): this is called self-sputtering and subject of research for several decades [63][64][65][66]. In the early implementations, non-planar (e.g.…”
Section: A Brief Look At Some Early Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For selected target materials with very high sputtering yield and/or vapor pressure (like Cu, Ag, Bi, Zn), high power operation of a magnetron can readily lead to ionization of the sputtered atoms, and the newly formed metal ions can at least in part take over the function of the sputtering gas (often argon): this is called self-sputtering and subject of research for several decades [63][64][65][66]. In the early implementations, non-planar (e.g.…”
Section: A Brief Look At Some Early Workmentioning
confidence: 99%
“…self-sputtering [64][65][66], which can run away to very high levels if the power supply is capable of delivering the necessary current at the required sputtering discharge voltage [154]. The most clear demonstration of self-sputtering is achieved when eliminating the process gas altogether, which can be done by turning off the gas supply after starting the discharge [155,156], or by choosing operation in high vacuum and starting HiPIMS pulses by a small "puff" of plasma from a short-pulse cathodic arc source [157,158].…”
Section: Pulsed Plasma Production By Hipimsmentioning
confidence: 99%
“…[11][12][13] By now it is well established that a large fraction of the sputtered atoms becomes ionized and participates in the sputtering process (self-sputtering 6,[14][15][16][17] ) by raising the peak power density by typically 2 orders of magnitude above the average value. 18,19 It has been demonstrated that the role of self-sputtering evolves as the pulse develops, however, the details of this evolution strongly depend on the target material.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed analysis of the deposition system and technology behind the deposition process has been discussed previously. [3,4] There has been previous successful work detailed in regards to internal coating of surfaces with DLC; [5][6][7][8] however, it is believed that the properties of high deposition rate, low stress with thick films [9] and the technology behind the deposition process will add some novel theory behind producing DLC films. Table 1 shows typical deposition conditions for growing the described films.…”
Section: Experimental Partmentioning
confidence: 99%